Two Lattice Boltzmann Models for Three-Dimensional Coupled Burgers’ Equations (Advances in Applied Mathematics and Mechanics, 2025)
Two lattice Boltzmann models are presented for the general three-dimensional coupled Burgers’ equations with different diffusion coefficients. The coupled parts or all of the convection items are treated as the source terms, where the spatial gradient can be calculated by the distribution function. The three-dimensional coupled Burgers’ equations can be exactly recovered from the lattice Boltzmann(LB) models through the direct Taylor expansion. Some numerical tests were performed to verify the accuracy and efficiency of the present models.